The ABCs of entrustable professional activities: an overview of 'entrustable professional activities' in medical education. Issue 9 (16th September 2016) - El‐Haddad, C.; Damodaran, A.; McNeil, H. P.; Hu, W.
Abstract : Consultants regularly need to decide whether a trainee can be entrusted to perform a clinical activity independently. 'Entrustable professional activities' (EPA) provide a framework for justifying and better utilising supervisor entrustment decisions for trainee feedback and assessment in the workplace. Since being proposed by Olle ten Cate in 2005, EPA are emerging as an integral part of many international medical curricula, and are being considered by the Royal Australasian College of Physicians in the current review of physician training. EPA are defined as tasks or responsibilities that can be entrusted to a trainee once sufficient competence is reached to allow for unsupervised practice. An example might be to entrust a trainee to 'Initiate and co‐ordinate care of the palliative patient' with only off‐site or indirect supervision. Rather than attempting to measure directly each of the many separate competencies required to undertake such a complex task, EPA direct the trainee and supervisor's attention to the trainee's performance in a limited number of selected, representative, important day‐to‐day activities. EPA‐based assessment is gaining momentum, amongst significant concerns regarding feasibility of implementation. While the optimal process for designing and implementing EPA remains to be determined, it is an assessment strategy where the over‐arching goal of optimal patient care remains in clear sight. This review explores the central role of trust in medical training, the case for EPA and potential barriers to implementing EPA‐based assessment.